Micro analytical and magnetic characterization of aluminum-iron spinel (FeAl2O4) synthesized by combustion reaction. Issue 11 (1st August 2020) - Silva, J.M.; Araújo, J.F.D.F.; Brocchi, E.; Solórzano, I.G.
Abstract: Materials with spinel structures have the general stoichiometric formula AB2 O4. Their constituent elements A and B determine specific properties, some of important technological interest, particularly related to magnetic behavior. In the present study Aluminum–Iron, single-phase spinel, rarely found in nature, has been synthesized via combustion reaction. The presence and amount of urea as combustion source has been varied in order to verify its influence on the microstructure and magnetic properties of the product material. X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) have been used to characterize the synthesized powders. The microstructural analysis indicated that the sample synthesized without urea as fuel corresponds to iron and aluminum oxides, but mostly amorphous, with low intensity X-ray diffraction peaks corresponding to Hematite particles. The samples produced with urea displayed in their X-ray diffractogram well defined peaks allowing to index the crystallographic planes of the constitutive phases: spinel and magnetite. Among these, the sample synthesized with stoichiometric amount of urea indicate being constituted by single-phase FeAl2 O4 spinel. However, the samples synthesized with excess and deficiency of urea showed, besides the production of the desired spinel, the formation of Fe3 O4 have occurred. Magnetic measurements indicate that samples synthesized with urea behave as a ferromagnetic material, while samples produced without urea exhibits paramagnetic behavior.